NUMERICAL ANALYSIS OF IN-PLANE BEHAVIOUR OF MASONRY INFILLED RC FRAMES USING MACRO AND MICRO MODELS - KAREEM, KAMARAN MOHAMMED; ALI, HUNAR FARID HAMA; SHARIF, HIWA HAMED; HASSAN, BEDAR RAUOF; MAHMOD, FARAYDON HAMA RASH W. (Journal of Duhok University, 2021)
A number of simplified methodologies have been proposed aiming at preparing numerical tools suitable for engineering application, to predict the nonlinear seismic behavior of infilled frame structures. In this paper, a 2D discrete macro element model (DMEM) for the simulation of the in-plane behavior of RC frames with infill walls, is presented, validated with an experimental result that investigate the influence of infill masonry, and evaluated with a proposed Finite Element model (FEM). In this model, the frame members are modeled by beam-column elements with lumped plasticity, while the infills contribution are modeled by plane discrete-element. As an extended study, a 2D prototype of multistory frame building, for which the results of pseudo dynamic tests are available, is investigated. The ability of the considered DMEM to predict the in-plane behavior of infill masonry elements is investigated, the merits and drawbacks are highlighted.